Pengaruh Produksi Gula Domestik, Jumlah Penduduk, dan Harga Gula Internasional terhadap Impor Gula di Indonesia - Raissa Syaharani; Dicky Iranto; Fitra Dila Lestari (Indo Publishing, 2026)
This study aims to determine the effects of domestic sugar production, population size, and international sugar prices on sugar imports in Indonesia. This study employs a quantitative approach using secondary time-series data sourced from the BPS, the Directorate General of Plantations, Worldometer, and the World Bank, covering the period from 1994 to 2024. The data analysis technique used in this study is multiple linear regression, processed using the E-Views 12 software. The results of this study indicate that domestic sugar production has a negative but insignificant effect on sugar imports in Indonesia. Population size has a positive and significant effect on sugar imports in Indonesia. International sugar prices have a negative but insignificant effect on sugar imports in Indonesia.